2022
DOI: 10.46328/ijemst.2166
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Healthy Gymnastics and Use of Technology as an Effort to Maintain Body Immunity during the Pandemic

Abstract: Exercise is one way to prevent the spread of the COVID-19 virus. Aerobic exercise is a very popular choice for many people. Therefore, this study aims to develop exercise in maintaining and improving aerobic health. One of the most popular aerobic sports is gymnastics. In addition, with the development of aerobic exercise, it is also hoped that people will be more interested in exercising. Research and development methods are used in this study to produce and test the developed product's effectiveness. In carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
12

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
0
5
0
12
Order By: Relevance
“…A person's motivation may also serve as the foundation for their involvement and participation in a program. It requires discipline and learning desire for kids to be motivated to learn (Paramitha et al, 2022). Previous research have shown that learning motivation is connected to students' mathematical success, which may be used to examine the aforementioned theoretical hypotheses (Jehadus et al, 2022).…”
Section: Learning Motivationmentioning
confidence: 99%
“…A person's motivation may also serve as the foundation for their involvement and participation in a program. It requires discipline and learning desire for kids to be motivated to learn (Paramitha et al, 2022). Previous research have shown that learning motivation is connected to students' mathematical success, which may be used to examine the aforementioned theoretical hypotheses (Jehadus et al, 2022).…”
Section: Learning Motivationmentioning
confidence: 99%
“…Pertama terkait cara yang paling efektif adalah dengan sosialisasi harapan kesejahteraan yang digantungkan kepada pemimpin, dalam artian menyebarluaskan aktifitas-aktifitas politik yang akan menjadi bulan-bulanan kacamata masyarakat Indonesia untuk menilai dan memahami bagaimana politik itu bekerja, sehingga masyarakat akan mengerti apa dampak atau efek domino yang terjadi saat hak dalam perpolitikan tiap-tiap masyarakat digunakan. Kemudian hipotesis terkait masalah yang kedua, hambatan yang kerap kali menghambat masyarakat dalam memahami atau menyadari sebuah fungsi politik adalah tuntutan konservatif yang memang terbentuk dari masa ke masa, dimaksudkan bahwa hal tersebut terjadi karena beredarnya streotip bahwa politik bukan semata-mata berkaitan dengan pemerintahan, namun berkaitan dengan unsur kejahatan kriminal, maka dari itu kesadaran berpolitik masyarakat cenderung untuk membuat batasan, ataupun acuh tak acuh terhadap kondisi pemerintahan yang mana dominan akan fenomena politik didalamnya (Paramitha et al, 2022).…”
Section: Pendahuluanunclassified
“…Orang bersuku Batak meyakini sebelum agama Kristen maupun Islam masuk ke wilayah Batak, semua orang Batak adalah pengikut Parmalim. Tetapi, dengan masuknya agama Kristen dan Islam pada abad ke-19, jumlah pengikut Parmalim menurun, bahkan secara drastis (Paramitha et al, 2022). Hubungan parmalim dan masyarakat terjalin dengan rukun, dikarenakan di tanah Batak Sumatera Utara toleransi dan hidup rukun bukan karena dukungan ajaran agama tetapi karena tradisi budaya dari adat dalian natolu.…”
Section: Hasil Dan Pembahasanunclassified